Frequency of rare mutations and common genetic variations in severe hypertriglyceridemia in the general population of Spain. Issue 1 (December 2016) - Lamiquiz-Moneo, Itziar; Blanco-Torrecilla, Cristian; Bea, Ana; Mateo-Gallego, Rocío; Pérez-Calahorra, Sofía; Baila-Rueda, Lucía; Cenarro, Ana; Civeira, Fernando; de Castro-Orós, Isabel
Abstract Background Hypertriglyceridemia (HTG) is a common complex metabolic trait that results of the accumulation of relatively common genetic variants in combination with other modifier genes and environmental factors resulting in increased plasma triglyceride (TG) levels. The majority of severe primary hypertriglyceridemias is diagnosed in adulthood and their molecular bases have not been fully defined yet. The prevalence of HTG is highly variable among populations, possibly caused by differences in environmental factors and genetic background. However, the prevalence of very high TG and the frequency of rare mutations causing HTG in a whole non-selected population have not been previously studied. Methods The total of 23, 310 subjects over 18 years from a primary care-district in a middle-class area of Zaragoza (Spain) with TG >500 mg/dL were selected to establish HTG prevalence. Those affected of primary HTG were considered for further genetic analisys. The promoters, coding regions and exon-intron boundaries ofLPL, LMF1, APOC2, APOA5, APOE andGPIHBP1 genes were sequenced. The frequency of rare variants identified was studied in 90 controls. Results One hundred ninety-four subjects (1.04 %) had HTG and 90 subjects (46.4 %) met the inclusion criteria for primary HTG. In this subgroup, nine patients (12.3 %) were carriers of 7 rare variants inLPL, LMF1, APOA5, GPIHBP1 orAPOE genes. Three of these mutations are described for the first time in this work. The presence of a rare pathogenic mutation did not confer a differential phenotype or a higher family history of HTG. Conclusion The prevalence of rare mutations in candidate genes in subjects with primary HTG is low. The low frequency of rare mutations, the absence of a more severe phenotype or the dominant transmission of the HTG would not suggest the use of genetic analysis in the clinical practice in this population.